Tourism Department Communication Strategy in Promoting Sharia Tourism Objects in Simeulue Regency - Azhari, Muhammad; Khairina, Ulfa; Irawan, Andi (ISTIFHAM, 2023)
The Department of Culture and Tourism has been promoted through social media and print media and by holding national and international events inviting tourists to visit Simeulue Island. The impact of the promotion carried out by the Simeulue Regency Tourism Office, Simeulue Regency tourism is already known worldwide, especially water tourism (surfing). In 2019, more than a thousand foreign tourists visited Simeulue, but since 2020, due to the Covid-19 pandemic, the number of foreign tourists coming to Simeulue has decreased. This research aims to discover the communication strategy of the Tourism Department in Simeulue Regency in promoting local wisdom tourism and the obstacles faced by the Tourism Department in promoting local wisdom tourism destinations in Simeulue Regency. This research uses qualitative research methods with interview, observation and documentation techniques. Data analysis uses descriptive qualitative. The research shows that the communication strategy of the Tourism Office in Simeulue Regency in promoting local wisdom tourism is carried out by fostering tourist destinations owned by Simeulue Regency. Promotion is carried out through print media in the form of brochures, electronic television media broadcast on TV Aceh, festivals, events and expos, and social media by showing videos of tourist destinations via the YouTube channel. The obstacles faced by the Tourism Office in promoting local wisdom tourism destinations in Simeulue Regency are lack of budget for promotion, lack of understanding of human resources regarding developing tourism potential, lack of network and disruption of internet and electricity networks.